Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Kepuasan Kerja Karyawan Pada PT. Dunia Plastik Raya Karangploso, Kabupaten Malang - Haris, Haris; Mansur, Muhammad; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the influence of the work environment and compensation on employee job satisfaction at PT. Dunia Plastik Raya partially or simultaneously. The population used in this research was all employees at PT. Dunia Plastik Raya numbers 40 people. Respondents in this research were employees at PT. Greater Plastic World. This population consists of 40 employees, so the sampling technique used in this research is a saturated sampling technique (census sample). Data analysis used SPSS 25 with multiple linear regression. The results of the research partially show that the work environment has a positive and significant effect on employee satisfaction, compensation has a positive and significant effect on employee satisfaction. Simultaneously the work environment and compensation have a significant effect on employee satisfaction at PT. Greater Plastic World. Keywords: work environment, compensation, and employee satisfaction